In vitro synthesis of oncogenic human papillomaviruses requires episomal genomes for differentiation-dependent late expression. - Frattini, M G (1996)
Human papillomavirus (HPV) types 16, 18, 31, and 51 are the etiologic agents of many anogenital cancers including those of the cervix. These "high risk" HPVs specifically target genital squamous epithelia, and their lytic life cycle is closely linked to epithelial differentiation. We have developed a genetic assay for HPV functions during pathogenesis using recircularized cloned HPV 31 genomes that were transfected together with a drug resistance marker into monolayer cultures of normal human foreskin keratinocytes, the natural host cell. After drug selection, cell lines were isolated that stably maintained HPV 31 DNA as episomes and underwent terminal differentiation when grown in organotypic raft cultures. In differentiated rafts, the expression of late viral genes, amplification of viral DNA, and production of viral particles were detected in suprabasal cells. This demonstrated the ability to synthesize HPV 31 virions from transfected DNA templates and allowed an examination of HPV functions during the vegetative viral life cycle. We then used this system to investigate whether an episomal genome was required for the induction of late viral gene expression. When an HPV 31 genome (31E1*) containing a missense mutation in the E1 open reading frame was transfected into normal human keratinocytes, the mutant viral sequences were found to integrate into the host cell chromosomal DNA with both early and late regions intact. While high levels of early viral gene transcription were observed, no late gene expression was detected in rafts of cell lines containing the mutant viral genome despite evidence of terminal differentiation. Therefore, the induction of late viral gene expression required that the viral genomes be maintained as extrachromosomal elements, and terminal differentiation alone was not sufficient. These studies provide the basis for a detailed examination of HPV functions during viral pathogenesis.